Charity and State in Late Renaissance Italy : the Monte di Pieta of Florence - Menning, Carol Bresnahan (Cornell University Press, 2019)
Drawing on extensive archival evidence, Carol Bresnahan Menning examines the remarkable evolution of the Florentine monte from a small charitable pawnshop to a flourishing savings organization and a powerful instrument of patronage and state finance.